Recurrent apnea in an infant with pertussis due to household transmission. Issue 3 (28th January 2017) - Ochi, Motoharu; Nosaka, Nobuyuki; Knaup, Emily; Tsukahara, Kohei; Kikkawa, Tomonobu; Fujii, Yousuke; Yashiro, Masato; Sato, Keiji; Ugawa, Toyomu; Okada, Ayumi; Tsukahara, Hirokazu
Key Clinical Message: Bordetella pertussis causes life‐threatening apnea in infants. Lymphocytosis is an important clue for diagnosis and for determining the severity of pertussis. Antibiotics do not shorten or ameliorate the disease and only decrease the risk of transmission. Antepartum maternal immunization is important for preventing pertussis in infants. Abstract : Bordetella pertussis causes life‐threatening apnea in infants. Lymphocytosis is an important clue for diagnosis and for determining the severity of pertussis. Antibiotics do not shorten or ameliorate the disease and only decrease the risk of transmission. Antepartum maternal immunization is important for preventing pertussis in infants.